Caso de estudio: Impacto de la pandemia originada por el COVID-19 en la exportación de cacao en el año 2020 - Herrera Bellido, Jorge Tomas (2023)
In recent decades, the cultivation of cocoa has been gaining relevance for Peru, managing to position the country among the ten largest cocoa producers worldwide. Being a very important crop for the subsistence of many families, it is proposed in the present research work to identify the influence of the pandemic generated by the Sars-Cov2 virus, commonly called Covid-19 or coronavirus in cocoa exports for the period most critical of the pandemic that was in 2020, both for Peru and for Ecuador, which is a direct competitor of Peruvian cocoa. In order to determine if the effect of Covid-19 has been significant on exports, the T-Student statistical method has been used for related samples, which has been complemented with a qualitative analysis. From the results it was observed that, although Peru slightly reduced its cocoa exports due to the decrease in demand in 2020, the effect of Covid-19 was not statistically significant, since levels were similar to those obtained in 2019.In the Ecuadorian case, it was appreciated that, unlike Peru, Covid-19 did have a significant positive effect by achieving an increase of almost 24% in the value of its exports in 2020, compared to those of 2019. This difference between Peru and Ecuador basically responds to the destination of their exports, and that is that importers of Ecuadorian cocoa have demanded a greater volume than their Peruvian partners, and it has even been seen that some important importers of Peruvian cocoa have replaced it with Ecuadorian cocoa.